Facile synthesis of 4H-chromene derivatives via base-mediated annulation of ortho-hydroxychalcones and 2-bromoallyl sulfones - Thadkapally, Srinivas; Kunjachan, Athira C.; Menon, Rajeev S. (Beilstein Journal of Organic Chemistry, 2016)
The cesium carbonate-mediated reaction of 2-bromoallyl sulfones and ortho-hydroxychalcones furnished 3-arylsulfonyl-4H-chromene derivatives in 58–67% yield (18 examples). 2-Bromoallyl sulfones functioned as synthetic surrogates for allenyl sulfones in the reaction.
Keywords: allenes; chromenes; cyclocondenzation; sulfones; vinylic substitution